UNDERSTANDING BOLLYWOOD CULT FILMS: EXPLORING THEIR ROLE IN CHANGING CONVENTIONS AND IMPACTING NEW THOUGHTS IN INDIAN YOUTH, SOCIETY AND CULTURE: English - Swarnakar, Santosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores the impact of Bollywood cult films on Indian society and culture, focusing on how they challenge preconceived notions and promote original thought. Cult films often address taboo topics and minority perspectives, encouraging viewers to think critically and explore alternative options. These films reflect social and cultural shifts in India, highlighting the concerns and opinions of younger generations and building passionate fan followings. Despite having a low return on investment, many cult films have a long-lasting influence, sometimes serving as catalysts for social and cultural movements and impacting the careers of performers and filmmakers. The study highlights the importance of filmmakers considering the social impact of their work and using their platform to support ideals that promote peace, justice and social harmony. Researchers and students interested in the film industry, popular culture and society can use this data to examine and compare various cult films and understand their cultural and social values. The results of this research can be used by scholars, students and researchers to better understand the cultural and social significance of Bollywood cult films and their impact on Indian society and culture.